CD24 is an independent prognostic marker of survival in nonsmall cell lung cancer patients - Kristiansen, G (Nature Publishing Group, 2003)
Originally identified as a B-cell marker, expression of the cell surface molecule CD24 has meanwhile been observed in a variety of human malignancies. It appears to function as a ligand of P-Selectin, an adhesion molecule that is present in activated platelets and endothelial cells. We aimed to determine the rate of CD24 expression in our nonsmall cell lung cancer (NSCLC) collection and to clarify its correlation with clinicopathological parameters including patients' survival. A total of 89 NSCLC were analysed immunohistochemically using a monoclonal CD24 antibody (clone 24C02) and a standard detection system (LSAB, DAKO) on NSCLC tissue microarrays (TMA). The staining was semiquantitatively scored (0, 1+, 2+, 3+) and grouped into high (2+, 3+)- and low (0, 1+)-level expression for statistical analysis. A high level of CD24 expression was observed in 45% of the cases, preferentially adenocarcinomas. Patients whose tumours had a high CD24 expression showed a significantly shorter median survival time of 23 months vs 38 months (P=0.033, log-rank test). Similarly tumour, grading, nodal status and clinical stage were significant prognostic markers in univariate survival analysis. Importantly, in the Cox regression-based multivariate analysis, CD24 expression (P=0.025) together with tumour stage (P=0.006) and grade (P=0.011) proved to be independent prognostic parameters. We hypothesise that the decreased survival of NSCLC patients with strongly CD24-positive tumours is related to an enhanced propensity of haematogenous metastasis formation, which might be P-Selectin mediated.